An experimental study on modulus of rupture and water absorption of cement-seashell power mortar - Nabila Shahilla, Rajagopal (2014)
The usage of cement itself in the industry is inadequate as the strength of the mortar produced is dependent on the properties as cement used. Seashell is a major of calcium carbonate compound and found to be a natural pozzolan. In this research, the use of seashell powder as additive to cement mortar is investigated. The effect of using seashell powder as additive on the modulus of rupture, force against deflection and the rate of water absorption of the mortar are investigated using varying percentage of 1%, 2%, 3% and 4% from the cement weight respectively.30 mortar beams with different percentage of seashell powder of 100mm x 100mm x 500mm were moulded and cured for 7 and 28 days respectively. Findings revealed cement-seashell powder mortar has higher modulus of rupture than controlled beam. The modulus of rupture decreases with the increase of the percentage of seashell powder of 4%. In addition, the mortar beam containing seashell powder can withstand higher forces compared to the controlled beam. All mortars containing seashell powder yielded lower porosity compared to the conventional mortar. This indicates that seashell powder has potential to be used as additive in cement replacement. Moreover, this study also concern of managing disposal of seashell waste in the future for conservation of environment.